Research trends in single-photon detectors based on superconducting wires - Francesco P. Venza; Marco Colangelo (APL Photonics)
Superconducting nanowire single-photon detectors (SNSPDs) are the leading technology for photon counting at near-infrared wavelengths, offering unparalleled performance across multiple metrics and enabling diverse applications. Two decades after their introduction, SNSPDs have made significant progress and reached a mature stage of development. However, the requirements of new, demanding applications and the push to democratize this technology open up new opportunities for further advancements. In this perspective, we provide an introduction to SNSPD technology, an overview of current research trends, and insights into future directions in this field.